Axial Load Of Built-Up C-Section Cold-Formed Steel With An Opening - Wan Anis Zulaikha, Wan Nor Harisan (2023)
Cold-formed steel (CFS) members are constructed from structural quality sheet steel that has been roll-formed through a number of dies into C-sections and other shapes. The name "cold-formed steel" refers to the fact that no heat is used to produce the shapes (unlike hot-rolled steel). For a wide range of structural and non-structural purposes, different steel thicknesses are offered. According to their use and purpose in construction projects, cold-formed steel is available in a variety of section types. Single open sections, open built-up sections, and closed built-up sections are the three primary types of sections. This study will focus on open built-up C-sections. Perforations are typically seen in structural members made of cold-formed steel. Cold-formed steel is given perforations, which are holes or openings, to facilitate construction operations. Depending on its purpose, it is typically offered in a variety of sizes and shapes to accommodate plumbing, electrical, and air conditioning or heating services. Nevertheless, depending on the placement, size, and orientation of the opening, the existence of perforations may result in a drop in the strength of both the member's overall strength and its individual component parts. This study will involve one type of 20mm diameter opening that will be made on the specimen and will concentrate on the impact of the existence of an opening and the buckling shape behavior of the specimen. To examine the impact of an opening on the load capacity of column members of builtup C-section, an experimental examination of cold-formed steel exposed to compression loading is being held. In this experiment, a total of 2 different conditions which have 3 samples for each condition with the existence of an opening were evaluated. Each member was compressed and has a nominal thickness of 0.8 mm, a column length of 600 mm also 20 mm diameter of an opening is being used for this test. The outcome of this experiment is to see the comparison in terms of ultimate strength and buckling shape behavior between built-up C-section with an opening and also without an opening